TOPF MONGE, Guiomar. Traducir el género. Aproximación feminista a las traducciones españolas de obras de Annemarie Schwarzenbach. Berlín, Peter Lang, 2020, 316 pp., ISBN 978-36-318-3260-8 - Álvarez Sánchez, Patricia (Hikma, 2023)
.